2005
DOI: 10.1143/jjap.44.2546
|View full text |Cite
|
Sign up to set email alerts
|

InGaAs/AlGaAs Quantum Wire DFB Buried HeteroStructure Laser Diode by One-Time Selective MOCVD on Ridge Substrate

Abstract: A quasi-buried heterostructure (BH) quantum wire (QWR)-distributed feedback (DFB) laser was realized by one-time selective metalorganic chemical vapor deposition (MOCVD) on a ridge substrate with a submicron grating. One-time selective MOCVD led to the formation of a ridge waveguide with a BH structure and a QWR array for gain-guided DFB laser diode (LD) without additional etching or regrowth process. The threshold current is 15 mA, and the threshold current density is 850 A/cm 2 . A stable single longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…While there has been significant research effort towards vertical InN quantum wires, there is less prior work on horizontal InN wire arrays that could be more easily incorporated into full epitaxial devices. It has been previously shown in several III-V semiconductor systems that vicinal or high-index substrates enable the epitaxial growth of horizontal quantum wires with 1D optical and electrical properties [34][35][36][37][38][39][40][41]. Such substrates in the III-arsenides system include high-index (311) A GaAs and miscut (100) and (110) GaAs [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there has been significant research effort towards vertical InN quantum wires, there is less prior work on horizontal InN wire arrays that could be more easily incorporated into full epitaxial devices. It has been previously shown in several III-V semiconductor systems that vicinal or high-index substrates enable the epitaxial growth of horizontal quantum wires with 1D optical and electrical properties [34][35][36][37][38][39][40][41]. Such substrates in the III-arsenides system include high-index (311) A GaAs and miscut (100) and (110) GaAs [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown in several III-V semiconductor systems that vicinal or high-index substrates enable the epitaxial growth of horizontal quantum wires with 1D optical and electrical properties [34][35][36][37][38][39][40][41]. Such substrates in the III-arsenides system include high-index (311) A GaAs and miscut (100) and (110) GaAs [35][36][37]. For the III-nitrides, a horizontal quantum wire formation has been observed in MOCVD-grown N-polar AlGaN/GaN heterostructures on miscut sapphires [38,[40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that high electron mobility transistors (HEMTs) have a responsivity of about 3 kA=W as a photodetector [1]. Furthermore, we have been exploiting the possibility of forming a quantum nanostructure on a patterned substrate as a cost-effective way of realising a highperformance device without high-resolution lithography [2,3]. In this Letter, we report that a quantum wire FET has a very high responsivity of more than 100 kA=W, which is comparable to that of a PMT at a very low bias voltage of typically half a volt.…”
mentioning
confidence: 99%